CHEKHOV SPEAKS TO US - Igić, Rajko (Vojnosanitetski pregled, 2014)
Anton Pavlovich Chekhov (1860-1904) was a medical doctor and writer. Through his writing, Chekhov showed how the symbiosis of the muse and Æsculapius can work. Tolstoy was struck by Chekhov's originality. Chekhov is an artist of life...[he] has his own special form, like impressionists. In 1890, Chekhov traveled across Siberia to Sakhalin Island to study conditions in the site where Russian convicts were kept. His the Sakhalin Island (1893), made a huge impression on the Russian public. He described in details the brutal beatings of the prisoners that he witnessed first hand. Thanks to the influence of the medical doctors that followed Chekhov's report, the Czar abolished corporal punishment for women in 1897 and for men in 1904. Even today, torture and brutal treatment of prisoners occurs frequently in many prisons. Media reports clearly show the brutality. For serious crimes, death or life imprisonment may be necessary, but ongoing cruelty is not. Many of us remain ignorant of the inhumane behavior of prison guards. And, shockingly, some of the brutality is accompished with the help of staff physicians. Unfortunately, many of our top current physicians, scientsts, artists, and other influential people rarely rise their voices against such atrocities. Anton Pavlovich Chekhov has told us to be bold and to speak loudly when we recognize problems. The solution will come afterwards. Thus, from time to time, we hear bold voices that help us create more humane societies. We must make sure that they are heard. Key Words: Chekhov, medical doctors, prisoners, atrocities, brutal beatings, humane society